Influence of Cell Spacing on the Thermal Distribution of Lithium-Ion Batteries with Forced-Air Cooling - Mamani Aguilar, Julio Cesar; Quispe Herrera, Angie Cristina; Obispo Vasquez, Angel Eduardo; Jirón Vicente, Andres Guiseppe (LACCEI, 2025)
The adoption of electric vehicles has become a well-established initiative, driven by their sustainability and significant environmental advantages compared to combustion vehicles. However, it has been observed that the batteries of these vehicles encounter temperature-related challenges during their charge and discharge cycles. This study investigates the influence of cell spacing on airflow distribution and temperature within the module through computational simulations. Two configurations with separations of Sx = 20 mm and Sx = 23 mm are analyzed to evaluate their impact on thermal dissipation. The results indicate that when the cell spacing is smaller, the airflow exhibits a more enveloping pattern around the cells, promoting a more uniform thermal dissipation. However, in this configuration, the maximum temperature reaches approximately 328 K. Conversely, when the spacing increases to Sx = 23 mm, the airflow moves more rapidly through the module without fully surrounding the cells, creating higher temperature regions on the right side of the module and reaching a maximum temperature of 325 K. It is concluded that a smaller spacing improves thermal uniformity, while a larger spacing reduces the peak temperature but generates more pronounced thermal gradients. The correlation between airflow distribution and temperature underscores the importance of optimizing cell arrangement to enhance cooling efficiency.